Determinan Keberhasilan Revitalisasi Posyandu - Marianus Ketmoen; Pius Weraman; Muntasir Muntasir; Imelda Februati Ester Manurung; Sabina Gero (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the determinants of the success of posyandu revitalization, which are influenced by the activeness of posyandu cadres, education/training, incentives, infrastructure and community participation in the working area of ​​Nunpene Health Center and Bitefa Health Center, East Miomaffo District, TTU Regency. The type of research used is cross-sectional. The results showed that the tcount for the variables of cadre activity, education/training, incentives, infrastructure and community participation were 1,245, 1,202, 1,867, 6,996, and 13,406, respectively, with a significance value for each variable, namely 0.216, 0.232. , 0.065, 0.000, and 0.000. The fcount value obtained is 107,290 with a significance of 0.000. In conclusion, cadre activity, education/training, incentives, infrastructure, and community participation positively and significantly impact the revitalization of posyandu. Keywords: Cadre Activity, Posyandu Revitalization